2021
DOI: 10.1177/17455065211063291
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the problems faced by Iranian housewives during the COVID-19 quarantine period, and their adaption strategies: A qualitative study

Abstract: Background: Housewives have several problems during the quarantine phase; so, the current study was designed to describe the challenges faced by Iranian housewives during the quarantine period in relation to COVID-19 and compatibility measures for it. Methods: The current research employed a qualitative methodology and a traditional content analysis method on 34 quarantined women in Tehran. Purposive sampling and snowballing were used to find participants, and semi-structured interviews were used to gather dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…People usually turn to religious rituals to achieve peace and quiet in times of calamity and other unexpected and terrifying situations [ 25 , 26 ]. The COVID-19 outbreak was unexpected, and no one knew when the pandemic would end or whether there would be any way to avoid or treat it.…”
Section: Resultsmentioning
confidence: 99%
“…People usually turn to religious rituals to achieve peace and quiet in times of calamity and other unexpected and terrifying situations [ 25 , 26 ]. The COVID-19 outbreak was unexpected, and no one knew when the pandemic would end or whether there would be any way to avoid or treat it.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have stressed the significance of the economic cost of living in non-compliance with health recommendations, which is consistent with our findings. 29 - 31 The findings of the study by SoleimanvandiAzar et al, 2021, also revealed that many people were forced to continue their activities due to the society’s economic conditions and lack of fixed income, as well as the high cost of living, even in these critical situations where their lives and families were threatened. 7 Yosefi Leni et al, 2020, also demonstrated in an essay that the Iranian government's financial incapacity to safeguard the nation financially during quarantine drove the bulk of individuals who had to work every day to make ends meet to be present in numerous crowded areas and shopping malls.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19, which broke out in Wuhan, China, in December 2019, is a new member of a broader family of viruses that originally appeared in 2003, leading to respiratory infections ranging from a simple cold to an epidemic and even a pandemic ( 1 , 2 ). COVID-19, which is currently spreading worldwide ( 3 , 4 ), is the world's largest current threat to public health and is expected to be the deadliest epidemic of the last 100 years ( 5 – 7 ). Disease incidence and mortality rates of this virus indicate the far-reaching consequences of the disease in the future.…”
Section: Introductionmentioning
confidence: 99%